2014
DOI: 10.1103/physrevb.89.024302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the ferromagnetic resonance behavior of coupled rectangular and circular Ni80Fe20rings

Abstract: A systematic investigation of the dynamic behavior of Ni 80 Fe 20 ring arrays using broadband ferromagnetic resonance spectroscopy as a function of inter-ring spacing and ring thickness is presented. Four distinct resonance modes were found for rectangular rings compared to the two modes seen in circular rings of identical width due to the presence of sharp corners and nonuniform demagnetization field distribution. The resonance peaks were sensitive to the inter-ring spacing and the ring thickness due to magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Finite ferromagnetic elements with sizes on the nano-and micro-metre length scales have been extensively studied due to their diverse range of applications that include (bio)sensors, data storage systems, logic and signal-processing systems, spintronics, and microwave devices [1][2][3][4][5][6][7][8], among others. Presently magnetization and magnetoresistance studies have been conducted for several basic geometries, such as on disks and/or rings with either square, rectangular, circular, or elliptical shapes [4,[9][10][11][12][13][14][15][16], as well as cylindrical nanorods and nanotubes [17,18]. Among these, particular attention, both theoretical and experimental, has been directed towards circular nanorings that have a thickness much less than the inner and outer radii [17,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Finite ferromagnetic elements with sizes on the nano-and micro-metre length scales have been extensively studied due to their diverse range of applications that include (bio)sensors, data storage systems, logic and signal-processing systems, spintronics, and microwave devices [1][2][3][4][5][6][7][8], among others. Presently magnetization and magnetoresistance studies have been conducted for several basic geometries, such as on disks and/or rings with either square, rectangular, circular, or elliptical shapes [4,[9][10][11][12][13][14][15][16], as well as cylindrical nanorods and nanotubes [17,18]. Among these, particular attention, both theoretical and experimental, has been directed towards circular nanorings that have a thickness much less than the inner and outer radii [17,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the static behavior of magnetic rings including circular [7,8,9], elliptical [10,11] and rectangular rings [12,13] were extensively investigated. The switching properties of ferromagnetic ring elements have also been studied via magnetoresistance (MR) measurements [14,15,16].…”
Section: Andmentioning
confidence: 99%
“…This flux-closure VS is especially interesting since the magnetization (M) follows the ring edges either in a clockwise or counter-clockwise direction. Previously, the static behavior of magnetic rings including circular [7][8][9], elliptical [10,11] and rectangular rings [12,13] were extensively investigated. The switching properties of ferromagnetic ring elements have also been studied via magnetoresistance (MR) measurements [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Demagnetizing field, edge pinning and anisotropy of patterns are all supposed to be important for the magnetic properties of patterned films. [5,11,19] Although the ferromagnetic resonance (FMR) spectra of patterned films have been wisely researched, recent studies showed rich spin wave spectra of magnetic disks and rings at different magnetized states. [13,20,21] For example, when the magnetic field was applied in the film plane, the magnetic disks at remanence showed a magnetization transition from onion to vortex state depending on the magnitude of the applied field.…”
Section: Introductionmentioning
confidence: 99%